Emergency situations in rheumatology with a focus on systemic autoimmune diseases - Vymetal, Jiri; Skacelova, Martina; Smrzova, Andrea; Klicova, Anna; Schubertova, Marketa; Horak, Pavel; Zadrazil, Josef (Biomedical papers, 2016)
Background and Aim. Rheumatic diseases are commonly considered chronic conditions. However, acute manifestations can be very severe and represent a diagnostic problem. Examples are systemic lupus erythematosus with acute flare, glomerulonephritis, CNS disorders and catastrophic antiphospholipid syndrome, scleroderma with interstitial lung disease, pulmonary hypertension and renal crisis and polyangiitis with alveolar haemorhage and acute respiratory failure. This aim of this paper is to overview emergency situations which can be encountered in the care of patients with autoimmune systemic diseases and vasculitides.Methods: A Pubmed search for both original and review articles, recent textbooks and current guidelines related to rheumatic diseases with possible acute situations were included in this review article. Relevant image documentation was obtained at the site over the past several years of observation.Conclusions: This paper provides an overview of facts and emergency situations which can be encountered in the care of patients with autoimmune systemic diseases and vasculitides. It is directed at clinicians working in intensive care. It provides a differential diagnostic overview and information which is rare and commonly underestimated.
Keywords: SLE; scleroderma; polyangiitis; dermatomyositis; emergent